Chromium alloy container and metal-supported electrochemical cell
By employing a chromium alloy container with a chromium oxide adhesive portion having a high chromium content and specific crystal structures, the issue of chromium diffusion and adhesion failure is addressed, ensuring long-term container integrity.
Patent Information
- Application Number
- JP2024545044
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-10-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-10-05
AI Technical Summary
Chromium alloy containers face issues with the diffusion of chromium into glass seals, leading to decreased strength and adhesion failure over time, affecting both fuel cell containers and general chromium alloy containers.
The use of a chromium alloy container with an adhesive portion made of a chromium oxide, where the chromium content is 50 mol% or more, and the oxide is crystalline with a spinel-type or corundum-type crystal structure, to maintain adhesion between alloy members over a long period.
This solution effectively prevents chromium diffusion and maintains the adhesion between alloy members, ensuring the chromium alloy container's integrity and longevity.
Smart Images

Figure 0007657376000003 
Figure 0007657376000004 
Figure 0007657376000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a chromium alloy container and a metal-supported electrochemical cell. [Background technology]
[0002] Patent Document 1 discloses a chromium alloy container for housing a fuel cell. The chromium alloy container includes a first interconnector, a second interconnector, a separator, an anode frame, and a glass seal.
[0003] The first interconnector is connected to the air electrode of the fuel cell. The second interconnector is connected to the anode current collecting layer of the fuel cell. The separator is connected to the solid electrolyte of the fuel cell and separates the fuel gas and oxidant gas flow paths. The anode frame is disposed between the separator and the second interconnector. A glass seal bonds the first interconnector and the separator.
[0004] The first interconnector, the second interconnector, the separator and the fuel electrode frame are each made of a chromium alloy (for example, SUS430, SUS444, etc.) The glass seal is made of a glass material. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2015-156352 Summary of the Invention [Problem to be solved by the invention]
[0006] In the chromium alloy container described in Patent Document 1, the chromium contained in the first interconnector and the separator diffuses into the glass seal, which changes the composition of the glass seal and reduces its strength. As a result, the glass seal is deformed or cracked, making it impossible to maintain adhesion between the alloy members for a long period of time. This is a problem that is common to chromium alloy containers in general, not limited to containers that house fuel cells.
[0007] An object of the present invention is to provide a chromium alloy container and a metal-supported electrochemical cell capable of maintaining adhesion between alloy members for a long period of time. [Means for solving the problem]
[0008] A chromium alloy container according to a first aspect of the present invention comprises a first alloy member made of an alloy containing chromium, a second alloy member made of an alloy containing chromium, and a bonding part bonding the first alloy member and the second alloy member, the bonding part being made of an oxide mainly composed of chromium.
[0009] A chromium alloy container according to a second aspect of the present invention is the chromium alloy container according to the first aspect, wherein the chromium content in the metal elements in the oxide is 50 mol % or more.
[0010] A chromium alloy container according to a third aspect of the present invention is related to the first or second aspect, wherein the oxide is composed of at least one of chromium oxide and chromium manganese oxide.
[0011] A chromium alloy container according to a fourth aspect of the present invention is related to any one of the first to third aspects, in which the oxide is crystalline.
[0012] A chromium alloy container according to a fifth aspect of the present invention is related to the above-mentioned fourth aspect, wherein the oxide has a spinel type or corundum type crystal structure.
[0013] A chromium alloy container according to a sixth aspect of the present invention is related to any one of the first to fifth aspects, wherein the adhesive portion has a first layer disposed on the first alloy member and a second layer disposed between the first layer and the second alloy member, and an oxide constituting the second oxide layer is different from an oxide constituting the first oxide layer.
[0014] A seventh aspect of the present invention relates to the chromium alloy container according to the sixth aspect, and the adhesive portion has a third layer sandwiched between the second layer and the second alloy member. The oxide constituting the third layer is the same as the oxide constituting the first layer.
[0015] The chromium alloy container according to an eighth aspect of the present invention is related to the seventh aspect, wherein a thickness ratio of the thickest layer to the thinnest layer among the first layer, the second layer and the third layer is 5 or less.
[0016] A ninth aspect of the present invention relates to the chromium alloy container according to any one of the sixth to eighth aspects, and a contact region of the surface of the first alloy component that contacts the adhesive portion includes a first region that contacts the first layer and a second region that contacts the second layer. The second region is connected to the first region.
[0017] A chromium alloy container according to a tenth aspect of the present invention is the ninth aspect, and the adhesive portion is embedded in a bottomed recess formed between the first alloy member and the second alloy member. The number of layers of the adhesive portion exposed from an opening of the bottomed recess is greater than the number of layers of the adhesive portion disposed in the deepest part of the bottomed recess.
[0018] A chromium alloy container according to an eleventh aspect of the present invention is related to any one of the first to tenth aspects, wherein the adhesive portion is a seal for sealing the internal space.
[0019] A chromium alloy container according to a twelfth aspect of the present invention is the chromium alloy container according to any one of the first to tenth aspects, wherein the second alloy member has an embossed portion in contact with the first alloy member, and the adhesive portion adheres the embossed portion to the first alloy member.
[0020] A metal-supported electrochemical cell according to a thirteenth aspect of the present invention comprises a chromium alloy container according to any one of the first to twelfth aspects, and a cell body arranged on the chromium alloy container. The first alloy member has a plurality of communication holes that communicate with the internal space. The cell body is arranged on the first alloy member so as to cover the plurality of communication holes. Effect of the Invention
[0021] According to the present invention, it is possible to provide a chromium alloy container and a metal-supported electrochemical cell capable of maintaining the adhesion between alloy members for a long period of time. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a plan view of the electrolysis cell according to the first embodiment. [Diagram 2] FIG. 2 is a cross-sectional view taken along line AA in FIG. [Diagram 3] FIG. 3 is a partially enlarged view of FIG. [Figure 4] FIG. 4 is a cross-sectional view of an electrolysis cell according to a second embodiment. [Diagram 5] FIG. 5 is a partially enlarged view of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] 1. First embodiment
[0024] (Electrolysis cell 1) Fig. 1 is a plan view of an electrolysis cell 1 according to a first embodiment, and Fig. 2 is a cross-sectional view taken along line AA in Fig. 1.
[0025] The electrolysis cell 1 is an example of a "metal-supported electrochemical cell" according to the present invention.
[0026] The electrolysis cell 1 is formed in a plate shape extending in the X-axis and Y-axis directions. In this embodiment, the electrolysis cell 1 is formed in a rectangular shape extending in the Y-axis direction when viewed in a plan view from the Z-axis direction perpendicular to the X-axis and Y-axis directions. However, the planar shape of the electrolysis cell 1 is not particularly limited, and may be a polygon other than a rectangle, an ellipse, a circle, or the like.
[0027] As shown in FIGS. 1 and 2, the electrolysis cell 1 includes a cell body 2 and a chromium alloy container 3 .
[0028] (Cell body 2) The cell body 2 is placed on a chromium alloy container 3. The cell body 2 is supported by a metal support 10 (described later) in the chromium alloy container 3. The cell body 2 has a hydrogen electrode 6 (cathode), an electrolyte 7, a reaction prevention layer 8, and an oxygen electrode 9 (anode).
[0029] The hydrogen electrode 6, electrolyte 7, reaction prevention layer 8, and oxygen electrode 9 are laminated in this order in the Z-axis direction from the chromium alloy container 3 side. The hydrogen electrode 6, electrolyte 7, and oxygen electrode 9 are essential components, while the reaction prevention layer 8 is optional.
[0030] [Hydrogen pole 6] The hydrogen electrode 6 is disposed on a first main surface 12 of the metal support 10 .
[0031] A source gas is supplied to the hydrogen electrode 6 through each supply hole 11 of the metal support 10. The source gas contains at least water vapor (H2O).
[0032] When the raw material gas contains only H2O, the hydrogen electrode 6 produces H2 from the raw material gas in accordance with the electrochemical reaction of water electrolysis shown in the following formula (1).
[0033] Hydrogen electrode 6: H2O+2e - →H2+O 2- (1)
[0034] When the raw gas contains CO in addition to H2O, the hydrogen electrode 6 converts the raw gas into H2, CO, and O2 in accordance with the electrochemical reactions of co-electrolysis shown in the following formulas (2), (3), and (4). 2- Generate.
[0035] Hydrogen electrode 6: CO2+H2O+4e - →CO+H2+2O 2- (2) Electrochemical reaction of H2O: H2O+2e - →H2+O 2- (3) Electrochemical reaction of CO2: CO2+2e - →CO+O 2- (4)
[0036] H2 generated in the hydrogen electrode 6 flows out from each supply hole 11 of the metal support 10 into an internal space 3a, which will be described later.
[0037] The hydrogen electrode 6 is a porous body having electronic conductivity. The hydrogen electrode 6 contains nickel (Ni). In the case of co-electrolysis, Ni functions as an electronic conductor and also functions as a thermal catalyst that promotes the thermal reaction between the generated H2 and the CO2 contained in the raw gas to maintain an appropriate gas composition for methanation, Fischer-Tropsch (FT) synthesis, etc. The Ni contained in the hydrogen electrode 6 is basically present in the form of metal Ni during operation of the electrolysis cell 1, but may also be partially present in the form of nickel oxide (NiO).
[0038] The hydrogen electrode 6 may contain an ion-conductive material, such as yttria-stabilized zirconia (YSZ), calcia-stabilized zirconia (CSZ), scandia-stabilized zirconia (ScSZ), gadolinium-doped ceria (GDC), samarium-doped ceria (SDC), (La,Sr)(Cr,Mn)O3, (La,Sr)TiO3, Sr2(Fe,Mo)2O6, (La,Sr)VO3, (La,Sr)FeO3, and a mixed material of two or more of these.
[0039] The thickness of the hydrogen electrode 6 is not particularly limited, but may be, for example, 1 μm or more and 100 μm or less. The thermal expansion coefficient of the hydrogen electrode 6 is not particularly limited, but may be, for example, 12×10 ―6 / ℃ or more 20×10 -6 / °C or less.
[0040] The method for forming the hydrogen electrode 6 is not particularly limited, and may be a firing method, a spray coating method (such as a thermal spray method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, or a cold spray method), a PVD method (such as a sputtering method or a pulsed laser deposition method), or a CVD method.
[0041] [Electrolyte 7] The electrolyte 7 is formed on the hydrogen electrode 6. The electrolyte 7 is disposed between the hydrogen electrode 6 and the oxygen electrode 9. In this embodiment, the electrolyte 7 is sandwiched between the hydrogen electrode 6 and the reaction prevention layer 8 and connected to both of them.
[0042] The electrolyte 7 covers the hydrogen electrode 6 and also covers the area of the first main surface 12 of the metal support 10 that is exposed from the hydrogen electrode 6 .
[0043] The electrolyte 7 is a dense body having oxide ion conductivity. 2- is transferred to the oxygen electrode 9. The electrolyte 7 is made of an oxide ion conductive material. The electrolyte 7 can be made of, for example, YSZ, GDC, ScSZ, SDC, LSGM (lanthanum gallate), etc., with YSZ being particularly suitable.
[0044] The thickness of the electrolyte 7 is not particularly limited, but may be, for example, 1 μm or more and 100 μm or less. The thermal expansion coefficient of the electrolyte 7 is not particularly limited, but may be, for example, 10×10 ―6 / ℃ or more 12×10 ―6 / °C or less.
[0045] The method for forming the electrolyte 7 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.
[0046] [Reaction prevention layer 8] The reaction prevention layer 8 is disposed between the electrolyte 7 and the oxygen electrode 9. The reaction prevention layer 8 is disposed on the opposite side of the electrolyte 7 to the hydrogen electrode 6. The reaction prevention layer 8 prevents a layer with high electrical resistance from being formed due to a reaction between a constituent element of the electrolyte 7 and a constituent element of the oxygen electrode 9.
[0047] The reaction prevention layer 8 is made of an oxide ion conductive material, and may be made of GDC, SDC, or the like.
[0048] The porosity of the reaction prevention layer 8 is not particularly limited, but may be, for example, 0.1% to 50%. The thickness of the reaction prevention layer 8 is not particularly limited, but may be, for example, 1 μm to 50 μm.
[0049] The method for forming the reaction prevention layer 8 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.
[0050] [Oxygen pole 9] The oxygen electrode 9 is disposed on the opposite side of the hydrogen electrode 6 with respect to the electrolyte 7. In this embodiment, since the reaction prevention layer 8 is disposed between the electrolyte 7 and the oxygen electrode 9, the oxygen electrode 9 is connected to the reaction prevention layer 8. If the reaction prevention layer 8 is not disposed between the electrolyte 7 and the oxygen electrode 9, the oxygen electrode 9 is connected to the electrolyte 7.
[0051] The oxygen electrode 9 receives O transferred from the hydrogen electrode 6 through the electrolyte 7 according to the chemical reaction of the following formula (5): 2- produces O2 from
[0052] Oxygen electrode 9:2O 2- →O2+4e - (5)
[0053] The oxygen electrode 9 is a porous body having oxide ion conductivity and electron conductivity, and can be made of a composite material of one or more of (La,Sr)(Co,Fe)O3, (La,Sr)FeO3, La(Ni,Fe)O3, (La,Sr)CoO3, and (Sm,Sr)CoO3 and an oxide ion conductive material (such as GDC).
[0054] The porosity of the oxygen electrode 9 is not particularly limited, but may be, for example, 20% to 60%. The thickness of the oxygen electrode 9 is not particularly limited, but may be, for example, 1 μm to 100 μm.
[0055] The method for forming the oxygen electrode 9 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.
[0056] (Chrome alloy container 3) The chromium alloy container 3 has an internal space 3a through which the source gas supplied to the hydrogen electrode 6 and the reducing gas (H2 in this embodiment) generated in the hydrogen electrode 6 flow.
[0057] In this embodiment, the chromium alloy container 3 includes a metal support 10, a frame 20, an interconnector 30, a first seal portion 40, and a second seal portion 50. The internal space 3a is a space surrounded by the metal support 10, the frame 20, the interconnector 30, the first seal portion 40, and the second seal portion 50.
[0058] In this embodiment, one of the metal support 10 and the frame 20 is an example of the "first alloy member" according to the present invention, and the other is an example of the "second alloy member" according to the present invention. Also, in this embodiment, one of the frame 20 and the interconnector 30 is an example of the "first alloy member" according to the present invention, and the other is an example of the "second alloy member" according to the present invention.
[0059] [Metal support 10] The metal support 10 supports the cell body 2. In this embodiment, the metal support 10 is formed in a plate shape. The metal support 10 may be in the shape of a flat plate or a curved plate.
[0060] The metal support 10 is only required to be able to support the cell body 2, and its thickness is not particularly limited, but can be, for example, 0.1 mm or more and 2.0 mm or less.
[0061] As shown in FIG. 2, the metal support 10 has a plurality of supply holes 11, a first main surface 12 and a second main surface 13.
[0062] Each supply hole 11 penetrates the metal support 10 from the first main surface 12 to the second main surface 13. Each supply hole 11 opens to each of the first main surface 12 and the second main surface 13. Each supply hole 11 is covered by the cell body 2. Specifically, the opening of each supply hole 11 on the first main surface 12 side is covered by the hydrogen electrode 6. The opening of each supply hole 11 on the second main surface 13 side is connected to the internal space 3a.
[0063] Each supply hole 11 can be formed by mechanical processing (for example, punching), laser processing, chemical processing (for example, etching), or the like.
[0064] In this embodiment, each supply hole 11 is formed linearly along the Z-axis direction. However, each supply hole 11 may be inclined with respect to the Z-axis direction, and may not be linear. Furthermore, each supply hole 11 may be connected to another supply hole 11.
[0065] The first main surface 12 is provided on the opposite side to the second main surface 13. The cell body 2 is disposed on the first main surface 12. The frame 20 is joined to the second main surface 13 via a first seal portion 40.
[0066] The metal support 10 is made of an alloy containing Cr (chromium). Examples of such alloys include Fe-Cr alloy steel (stainless steel, etc.) and Ni-Cr alloy steel. The Cr content in the metal support 10 is not particularly limited, but may be 4% by mass or more and 30% by mass or less.
[0067] The metal support 10 may contain Ti (titanium) and / or Zr (zirconium). The Ti content in the metal support 10 is not particularly limited, but may be 0.01 mol% or more and 1.0 mol% or less. The Zr content in the metal support 10 is not particularly limited, but may be 0.01 mol% or more and 0.4 mol% or less. The metal support 10 may contain Ti as TiO2 (titania) or Zr as ZrO2 (zirconia).
[0068] [Frame 20] The frame 20 is a spacer for forming the internal space 3a. In this embodiment, the frame 20 is formed in an annular shape.
[0069] The frame 20 is joined to the metal support 10 via the first seal portion 40 , and is joined to the interconnector 30 via the second seal portion 50 .
[0070] The thickness of the frame 20 is not particularly limited, but may be, for example, 0.1 mm or more and 2.0 mm or less.
[0071] The frame 20 is made of an alloy containing Cr. Examples of such alloys include Fe-Cr alloy steel and Ni-Cr alloy steel. The Cr content in the frame 20 is not particularly limited, but may be 4% by mass or more and 30% by mass or less. The composition of the frame 20 may be the same as or different from that of the metal support 10.
[0072] [Interconnector 30] The interconnector 30 is disposed on the opposite side of the metal support 10 with respect to the frame 20. The interconnector 30 is a member for electrically connecting the electrolytic cell 1 to an external power source or another electrolytic cell.
[0073] In this embodiment, the interconnector 30 is formed in a plate shape. The interconnector 30 may be in the shape of a flat plate or a curved plate.
[0074] The interconnector 30 is joined to the frame 20 via the second seal portion 50 .
[0075] The thickness of the interconnector 30 is not particularly limited, but can be, for example, not less than 0.1 mm and not more than 2.0 mm.
[0076] The interconnector 30 is made of an alloy containing Cr. Examples of such alloys include Fe-Cr alloy steel and Ni-Cr alloy steel. The Cr content in the interconnector 30 is not particularly limited, but can be 4 mass% or more and 30 mass% or less. The composition of the interconnector 30 may be the same as or different from that of the metal support 10. The composition of the interconnector 30 may be the same as or different from that of the frame 20.
[0077] [First seal portion 40] The first seal portion 40 is disposed between the metal support body 10 and the frame body 20. The first seal portion 40 is joined to both the metal support body 10 and the frame body 20.
[0078] The first seal portion 40 seals the gap between the metal support 10 and the frame 20. This prevents the source gas supplied to the hydrogen electrode 6 and the reducing gas generated in the hydrogen electrode 6 from leaking to the outside through the gap between the metal support 10 and the frame 20. The detailed configuration of the first seal portion 40 will be described later.
[0079] [Second seal portion 50] The second seal portion 50 is disposed between the frame body 20 and the interconnector 30. The second seal portion 50 is joined to each of the frame body 20 and the interconnector 30.
[0080] The second seal portion 50 seals the gap between the frame 20 and the interconnector 30. This prevents the raw material gas supplied to the hydrogen electrode 6 and the reducing gas generated in the hydrogen electrode 6 from leaking to the outside through the gap between the frame 20 and the interconnector 30.
[0081] The configuration of the second seal portion 50 is the same as the configuration of the first seal portion 40, which will be described next, and therefore, in this embodiment, a description of the configuration of the second seal portion 50 will be omitted.
[0082] (Detailed configuration of the first seal portion 40) Fig. 3 is a partially enlarged view of Fig. 2. Fig. 3 shows a cross section of the first seal portion 40. The cross section shown in Fig. 3 is perpendicular to the second main surface 13 of the metal support 10.
[0083] The first seal portion 40 has a first adhesive portion 41 and a second adhesive portion 42. Each of the first adhesive portion 41 and the second adhesive portion 42 is an example of the "adhesive portion" according to the present invention.
[0084] [First adhesive part 41] The first adhesive portion 41 is disposed between the metal support 10 and the frame body 20. The first adhesive portion 41 is sandwiched between the metal support 10 and the frame body 20. The first adhesive portion 41 is formed in an annular shape so as to surround the internal space 3a. The first adhesive portion 41 functions as a seal for sealing the internal space 3a.
[0085] In this embodiment, the first adhesive portion 41 is embedded in a bottomed recess 60 formed between the metal support 10 and the frame 20. The cross section of the bottomed recess 60 is wedge-shaped. The bottomed recess 60 has a deepest part 60a and an opening 60b. The opening 60b opens toward the internal space 3a. The first adhesive portion 41 is exposed to the internal space 3a.
[0086] The first adhesive portion 41 is made of an oxide containing Cr as a main component (hereinafter, abbreviated as "Cr oxide"). This can suppress the diffusion of Cr from the metal support 10 and the frame 20 to the first adhesive portion 41 during the manufacture or operation of the electrolysis cell 1. Even if Cr diffuses from the metal support 10 and the frame 20 to the first adhesive portion 41, the effect on the composition of the first adhesive portion 41 is small, so that the strength of the first adhesive portion 41 can be suppressed from decreasing. Furthermore, since the metal support 10, the frame 20, and the first adhesive portion 41 all contain Cr, the mutual adhesiveness can be improved. Therefore, the adhesiveness between the metal support 10 and the frame 20 can be maintained for a long period of time.
[0087] In this embodiment, "mainly composed of Cr" means that the Cr content is the highest among the metal elements in the Cr oxide when the composition of the Cr oxide constituting the first adhesive portion 41 is analyzed by an energy dispersive spectroscopy (EDS) device. The Cr content is not particularly limited, but can be, for example, 20 mol% to 100 mol%.
[0088] The Cr content in the metal elements in the Cr oxide constituting the first adhesive portion 41 is preferably 50 mol % or more. This makes it possible to significantly suppress the diffusion of Cr contained in the metal support 10 and the frame 20 into the first adhesive portion 41.
[0089] The Cr oxide constituting the first adhesive portion 41 is preferably composed of at least one of chromium oxide and chromium manganese oxide. These oxides have a property of making it particularly difficult for Cr to diffuse, and therefore the durability of the first adhesive portion 41 can be improved.
[0090] Chromium oxides include Cr2O3, etc. Chromium manganese oxides include MnCr2O4 (spinel), Mn 1,5 Cr 1,5 O4 (spinel) and others.
[0091] The Cr oxide constituting the first adhesive portion 41 is preferably crystalline. This makes it possible to prevent the first adhesive portion 41 from being damaged due to a phase transition of the Cr oxide from amorphous to crystalline even when the electrolysis cell 1 is operated for a long period of time.
[0092] The Cr oxide constituting the first adhesive portion 41 preferably has a spinel or corundum crystal structure. These crystal structures have high symmetry, and therefore the thermal stress resistance of the first adhesive portion 41 can be improved.
[0093] Here, as shown in FIG. 3, the first adhesive portion 41 according to this embodiment is made up of a first layer 1A, a second layer 2A, and a third layer 3A.
[0094] The first layer 1A is disposed on a metal support 10. The first layer 1A is sandwiched between the metal support 10 and a second layer 2A. In this embodiment, the first layer 1A is made of Cr2O3.
[0095] The second layer 2A is disposed between the first layer 1A and the frame body 20. In this embodiment, since the first adhesive portion 41 has the third layer 3A, the second layer 2A is sandwiched between the first layer 1A and the third layer 3A. A part of the second layer 2A fills the deepest part 60a of the bottomed recess 60. The part of the second layer 2A that fills the deepest part 60a is sandwiched between the metal support 10 and the frame body 20.
[0096] The oxide constituting the second layer 2A is preferably different from the oxide constituting the first layer 1A. This makes it possible to stop cracks that attempt to propagate in the Z-axis direction from the first layer 1A toward the second layer 2A, or from the second layer 2A toward the first layer 1A, at the interface between the first layer 1A and the second layer 2A. In this embodiment, the second layer 2A is composed of chromium manganese oxide.
[0097] The third layer 3A is disposed on the frame 20. The third layer 3A is sandwiched between the second layer 2A and the frame 20. The oxide constituting the third layer 3A is preferably different from the oxide constituting the second layer 2A. This allows a crack that attempts to propagate in the Z-axis direction from the second layer 2A to the third layer 3A, or from the third layer 3A to the second layer 2A, to be stopped at the interface between the second layer 2A and the third layer 3A. In this embodiment, the third layer 3A is composed of Cr2O3.
[0098] The oxide constituting the third layer 3A is preferably the same as the oxide constituting the first layer 1A, which makes the first adhesive portion 41 have a symmetrical structure in the thickness direction parallel to the Z-axis direction, thereby improving the mechanical reliability of the first adhesive portion 41.
[0099] The thickness of the first layer 1A is not particularly limited, but may be, for example, 0.1 μm or more and 100 μm or less. The thickness of the second layer 2A is not particularly limited, but may be, for example, 0.1 μm or more and 100 μm or less. The thickness of the third layer 3A is not particularly limited, but may be, for example, 0.1 μm or more and 100 μm or less. The thickness of the first layer 1A is obtained by arithmetically averaging the thicknesses measured at three points that divide the first layer 1A into four equal parts in the surface direction perpendicular to the Z-axis direction. The thicknesses of the second layer 2A and the third layer 3A are also obtained in the same manner as the thickness of the first layer 1A.
[0100] It is preferable that the thickness ratio of the thickest layer to the thinnest layer among the first layer 1A, the second layer 2A, and the third layer 3A is equal to or less than 5. By reducing the variation in thickness of each layer in this manner, the mechanical reliability of the first adhesive portion 41 can be improved.
[0101] 3, the metal support 10 has a contact region 10S in contact with the first adhesive portion 41. In this embodiment, the contact region 10S is a part of the second main surface 13. The contact region 10S preferably includes a first region S1 in contact with the first layer 1A, and a second region S2 that is connected to the first region S1 at a connection point P1 and in contact with the second layer 2A. This makes it possible to stop a crack that propagates between the first layer 1A and the second layer 2A toward the inside (i.e., the side away from the internal space 3a) at the connection point P1.
[0102] 3, the frame 20 has a contact region 20S that contacts the first adhesive portion 41. The contact region 20S preferably includes a third region S3 that contacts the third layer 3A, and a fourth region S4 that is connected to the third region S3 at a connecting point P2 and contacts the second layer 2A. This makes it possible to stop a crack that propagates inward between the second layer 2A and the third layer 3A at the connecting point P2.
[0103] 3, the number of layers of the first adhesive portion 41 exposed from the opening 60b of the bottomed recess 60 is preferably greater than the number of layers of the first adhesive portion 41 disposed in the deepest part 60a of the bottomed recess 60. This results in a smaller number of interfaces between the layers on the side of the deepest part 60a than on the side of the opening 60b. This makes it possible to prevent cracks that tend to progress inward along the interfaces between the layers from reaching the deepest part 60a. In this embodiment, the number of layers of the first adhesive portion 41 exposed from the opening 60b is "3", and the number of layers of the first adhesive portion 41 disposed in the deepest part 60a is "1".
[0104] The first adhesive portion 41 can be formed by applying a paste containing Cr oxide onto at least one of the surfaces of the metal support 10 and the frame 20, and then performing a heat treatment while the metal support 10 and the frame 20 are in close contact with each other. The conditions for the heat treatment can be appropriately set, but can be, for example, 600° C. to 1100° C. and 0.5 hours to 24 hours.
[0105] [Second adhesive part 42] The second adhesive portion 42 is disposed between the metal support 10 and the frame body 20. The second adhesive portion 42 is sandwiched between the metal support 10 and the frame body 20. The second adhesive portion 42 is disposed on the opposite side of the internal space 3a with respect to the first adhesive portion 41. The second adhesive portion 42 is formed in an annular shape so as to surround the first adhesive portion 41. The second adhesive portion 42 functions as a seal for sealing the internal space 3a.
[0106] The second adhesive portion 42 is separated from the first adhesive portion 41 in the surface direction. The metal support 10 and the frame body 20 are in close contact with or integrated with each other between the first adhesive portion 41 and the second adhesive portion 42. In order to improve the electrical connectivity between the metal support 10 and the frame body 20, it is preferable that they are integrated by welding or brazing.
[0107] In this embodiment, the second adhesive portion 42 is embedded in a bottomed recess 70 formed between the metal support 10 and the frame body 20. The cross section of the bottomed recess 70 is wedge-shaped. The bottomed recess 70 has a deepest part 70a and an opening 70b. The opening 70b opens toward the external space 3b. The second adhesive portion 42 is exposed to the external space 3b.
[0108] The second adhesive portion 42 is made of Cr oxide. This can suppress the diffusion of Cr from the metal support 10 and the frame 20 to the second adhesive portion 42 during the manufacture or operation of the electrolysis cell 1. Even if Cr diffuses from the metal support 10 and the frame 20 to the second adhesive portion 42, the effect on the composition of the second adhesive portion 42 is small, so that the strength of the second adhesive portion 42 can be suppressed from decreasing. Furthermore, since the metal support 10, the frame 20, and the second adhesive portion 42 all contain Cr, the mutual adhesion can be improved. Therefore, the adhesion between the metal support 10 and the frame 20 can be maintained for a long period of time.
[0109] The Cr content of the metal elements in the Cr oxide constituting the second adhesive portion 42 can be, for example, 20 mol % or more and 100 mol % or less. The Cr content is preferably 50 mol % or more. This significantly suppresses the diffusion of Cr contained in the metal support 10 and the frame 20 into the second adhesive portion 42.
[0110] The Cr oxide constituting the second adhesive portion 42 is preferably composed of at least one of chromium oxide and chromium manganese oxide. These oxides have a property that Cr is particularly difficult to diffuse, and therefore the durability of the second adhesive portion 42 can be improved.
[0111] The Cr oxide constituting the second adhesive portion 42 is preferably crystalline. This makes it possible to prevent the second adhesive portion 42 from being damaged due to a phase transition of the Cr oxide from amorphous to crystalline even when the electrolysis cell 1 is operated for a long period of time.
[0112] The Cr oxide constituting the second adhesive portion 42 preferably has a spinel or corundum crystal structure. These crystal structures have high symmetry, and therefore the thermal stress resistance of the second adhesive portion 42 can be improved.
[0113] Here, as shown in FIG. 3, the second adhesive portion 42 according to this embodiment is composed of a first layer 1B, a second layer 2B, and a third layer 3B.
[0114] The first layer 1B is disposed on a metal support 10. The first layer 1B is sandwiched between the metal support 10 and a second layer 2B. In this embodiment, the first layer 1B is made of Cr2O3.
[0115] The second layer 2B is disposed between the first layer 1B and the frame body 20. In this embodiment, since the second adhesive portion 42 has the third layer 3B, the second layer 2B is sandwiched between the first layer 1B and the third layer 3B. A part of the second layer 2B fills the deepest part 70a of the bottomed recess 70. The part of the second layer 2B that fills the deepest part 70a is sandwiched between the metal support 10 and the frame body 20.
[0116] The oxide constituting the second layer 2B is preferably different from the oxide constituting the first layer 1B. This makes it possible to stop cracks that attempt to propagate in the Z-axis direction from the first layer 1B toward the second layer 2B, or from the second layer 2B toward the first layer 1B, at the interface between the first layer 1B and the second layer 2B. In this embodiment, the second layer 2B is composed of chromium manganese oxide.
[0117] The third layer 3B is disposed on the frame 20. The third layer 3B is sandwiched between the second layer 2B and the frame 20. The oxide constituting the third layer 3B is preferably different from the oxide constituting the second layer 2B. This allows a crack that attempts to propagate in the Z-axis direction from the second layer 2B toward the third layer 3B, or from the third layer 3B toward the second layer 2B, to be stopped at the interface between the second layer 2B and the third layer 3B. In this embodiment, the third layer 3B is composed of Cr2O3.
[0118] The oxide constituting the third layer 3B is preferably the same as the oxide constituting the first layer 1B. This makes the second adhesive portion 42 have a symmetrical structure in the thickness direction parallel to the Z-axis direction, thereby improving the mechanical reliability of the second adhesive portion 42.
[0119] The thickness of the first layer 1B is not particularly limited, but may be, for example, 0.1 μm or more and 100 μm or less. The thickness of the second layer 2B is not particularly limited, but may be, for example, 0.1 μm or more and 100 μm or less. The thickness of the third layer 3B is not particularly limited, but may be, for example, 0.1 μm or more and 100 μm or less. The thickness of the first layer 1B is obtained by arithmetically averaging the thicknesses measured at three points that divide the first layer 1B into four equal parts in the surface direction perpendicular to the Z-axis direction. The thicknesses of the second layer 2B and the third layer 3B are also obtained in the same manner as the thickness of the first layer 1B.
[0120] It is preferable that the thickness ratio of the thickest layer to the thinnest layer among the first layer 1B, the second layer 2B, and the third layer 3B is equal to or less than 5. By reducing the variation in thickness of each layer in this manner, the mechanical reliability of the second adhesive portion 42 can be improved.
[0121] 3, the metal support 10 has a contact region 10T in contact with the second adhesive portion 42. In this embodiment, the contact region 10T is a part of the second main surface 13. The contact region 10T preferably includes a first region T1 in contact with the first layer 1B, and a second region T2 that is connected to the first region T1 at a connection point Q1 and in contact with the second layer 2B. This makes it possible to stop a crack that propagates between the first layer 1B and the second layer 2B toward the inside (i.e., the side away from the external space 3b) at the connection point Q1.
[0122] 3, the frame 20 has a contact region 20T that contacts the second adhesive portion 42. The contact region 20T preferably includes a third region T3 that contacts the third layer 3B, and a fourth region T4 that is connected to the third region T3 at a connecting point Q2 and contacts the second layer 2B. This makes it possible to stop a crack that propagates inward between the second layer 2B and the third layer 3B at the connecting point Q2.
[0123] 3, the number of layers of the second adhesive portion 42 exposed from the opening 70b of the bottomed recess 70 is preferably greater than the number of layers of the second adhesive portion 42 disposed in the deepest part 70a of the bottomed recess 70. This results in a smaller number of interfaces between the layers on the side of the deepest part 70a than on the side of the opening 70b. This makes it possible to prevent cracks that tend to progress inward along the interfaces between the layers from reaching the deepest part 70a. In this embodiment, the number of layers of the second adhesive portion 42 exposed from the opening 70b is "3", and the number of layers of the second adhesive portion 42 disposed in the deepest part 70a is "1".
[0124] The second adhesive portion 42 can be formed by applying a paste containing Cr oxide onto at least one of the surfaces of the metal support 10 and the frame 20, and then performing a heat treatment while the metal support 10 and the frame 20 are in close contact with each other. The conditions for the heat treatment can be set appropriately, and can be, for example, 600° C. or higher and 1100° C. or lower, and 0.5 hours or higher and 24 hours or lower. The second adhesive portion 42 and the first adhesive portion 41 may be formed simultaneously.
[0125] 2. Second embodiment
[0126] (Electrolysis cell 1) 4 is a cross-sectional view of an electrolysis cell 1a according to the second embodiment. The electrolysis cell 1a is an example of the "metal-supported electrochemical cell" according to the present invention.
[0127] The electrolytic cell 1a according to the second embodiment differs from the electrolytic cell 1 according to the first embodiment in that the interconnector 30 has an embossed portion 31 and a debossed portion 32, and that the chromium alloy container 3 has a third adhesive portion 43. The following mainly describes these differences.
[0128] In this embodiment, one of the metal support 10 and the interconnector 30 is an example of the "first alloy member" according to the present invention, and the other is an example of the "second alloy member" according to the present invention. Also, the third adhesive portion 43 is an example of the "adhesive portion" according to the present invention.
[0129] As shown in Fig. 4, the interconnector 30 has a plurality of embossed portions 31 and a plurality of debossed portions 32. Although two embossed portions 31 and three debossed portions 32 are illustrated in Fig. 4, the numbers of the embossed portions 31 and the debossed portions 32 can be changed as appropriate.
[0130] The embossed portion 31 abuts against the second main surface 13 of the metal support 10. As a result, the metal support 10 is supported by the interconnector 30, and thus bending of the metal support 10 is suppressed. Note that the embossed portion 31 only needs to abut against the metal support 10, and does not need to be joined to the metal support 10.
[0131] The debossed portion 32 protrudes toward the side opposite to the metal support 10. The debossed portion 32 abuts against an external power source or another electrolytic cell.
[0132] The third adhesive portion 43 adheres the embossed portion 31 to the metal support 10. The third adhesive portion 43 is disposed around the tip portion of the embossed portion 31. The tip portion of the embossed portion 31 refers to the portion of the embossed portion 31 that abuts against the metal support 10. The third adhesive portion 43 is preferably formed in a ring shape so as to surround the tip portion of the embossed portion 31. This can improve the adhesion between the embossed portion 31 and the metal support 10.
[0133] Here, Fig. 5 is a partially enlarged view of Fig. 4. Fig. 5 illustrates a cross section of the third adhesive portion 43. The cross section illustrated in Fig. 5 is perpendicular to the second main surface 13 of the metal support 10.
[0134] The third adhesive portion 43 is disposed between the metal support 10 and the embossed portion 31. The third adhesive portion 43 is sandwiched between the metal support 10 and the embossed portion 31. The third adhesive portion 43 is disposed on the metal support 10, and is formed in an annular shape so as to surround the tip portion of the embossed portion 31.
[0135] In this embodiment, the third adhesive portion 43 is embedded in a bottomed recess 80 formed between the metal support 10 and the embossed portion 31. The cross section of the bottomed recess 80 is wedge-shaped. The bottomed recess 80 has a deepest part 80a and an opening 80b. The opening 80b opens toward the internal space 3a. The third adhesive portion 43 is exposed to the internal space 3a.
[0136] The third adhesive portion 43 is made of Cr oxide. This can suppress the diffusion of Cr from the metal support 10 and the embossed portion 31 to the third adhesive portion 43 during the manufacture or operation of the electrolysis cell 1a. Even if Cr diffuses from the metal support 10 and the embossed portion 31 to the third adhesive portion 43, the effect on the composition of the third adhesive portion 43 is small, so that the strength of the third adhesive portion 43 can be suppressed from decreasing. Furthermore, since the metal support 10, the embossed portion 31, and the third adhesive portion 43 all contain Cr, the mutual adhesiveness can be improved. Therefore, the adhesiveness between the metal support 10 and the embossed portion 31 can be maintained for a long period of time.
[0137] The Cr content of the metal elements in the Cr oxide constituting the third adhesive portion 43 can be, for example, 20 mol % or more and 100 mol % or less. The Cr content is preferably 50 mol % or more. This significantly prevents the Cr contained in the metal support 10 and the embossed portion 31 from diffusing into the third adhesive portion 43.
[0138] The Cr oxide constituting the third adhesive portion 43 is preferably composed of at least one of chromium oxide and chromium manganese oxide. These oxides have a property that Cr is particularly difficult to diffuse, and therefore the durability of the third adhesive portion 43 can be improved.
[0139] The Cr oxide constituting the third adhesive portion 43 is preferably crystalline. This makes it possible to prevent the third adhesive portion 43 from being damaged due to a phase transition of the Cr oxide from amorphous to crystalline even when the electrolysis cell 1a is operated for a long period of time.
[0140] The Cr oxide constituting the third adhesive portion 43 preferably has a spinel or corundum crystal structure. These crystal structures have high symmetry, and therefore the thermal stress resistance of the third adhesive portion 43 can be improved.
[0141] Here, as shown in FIG. 5, the third adhesive portion 43 according to this embodiment is composed of a first layer 1C, a second layer 2C, and a third layer 3C.
[0142] The first layer 1C is disposed on a metal support 10. The first layer 1C is sandwiched between the metal support 10 and a second layer 2C. In this embodiment, the first layer 1C is made of Cr2O3.
[0143] The second layer 2C is disposed between the first layer 1C and the embossed portion 31. In this embodiment, since the third adhesive portion 43 has the third layer 3C, the second layer 2C is sandwiched between the first layer 1C and the third layer 3C. A part of the second layer 2C fills the deepest portion 80a of the bottomed recess 80. The part of the second layer 2C that fills the deepest portion 80a is sandwiched between the metal support 10 and the embossed portion 31.
[0144] The oxide constituting the second layer 2C is preferably different from the oxide constituting the first layer 1C. This makes it possible to stop cracks that attempt to propagate in the Z-axis direction from the first layer 1C to the second layer 2C, or from the second layer 2C to the first layer 1C, at the interface between the first layer 1C and the second layer 2C. In this embodiment, the second layer 2C is made of chromium manganese oxide.
[0145] The third layer 3C is disposed on the embossed portion 31. The third layer 3C is sandwiched between the second layer 2C and the embossed portion 31. The oxide constituting the third layer 3C is preferably different from the oxide constituting the second layer 2C. This allows a crack that attempts to propagate in the Z-axis direction from the second layer 2C to the third layer 3C, or from the third layer 3C to the second layer 2C, to be stopped at the interface between the second layer 2C and the third layer 3C. In this embodiment, the third layer 3C is composed of Cr2O3.
[0146] The oxide constituting the third layer 3C is preferably the same as the oxide constituting the first layer 1C. This makes the third adhesive portion 43 have a symmetrical structure in the thickness direction parallel to the Z-axis direction, thereby improving the mechanical reliability of the third adhesive portion 43.
[0147] The thickness of the first layer 1C is not particularly limited, but may be, for example, 0.1 μm or more and 100 μm or less. The thickness of the second layer 2C is not particularly limited, but may be, for example, 0.1 μm or more and 100 μm or less. The thickness of the third layer 3C is not particularly limited, but may be, for example, 0.1 μm or more and 100 μm or less. The thickness of the first layer 1C is obtained by arithmetically averaging the thicknesses measured at three points that divide the first layer 1C into four equal parts in the surface direction perpendicular to the Z-axis direction. The thicknesses of the second layer 2C and the third layer 3C are also obtained in the same manner as the thickness of the first layer 1C.
[0148] It is preferable that the thickness ratio of the thickest layer to the thinnest layer among the first layer 1C, the second layer 2C, and the third layer 3C is equal to or less than 5. By reducing the variation in thickness of each layer in this manner, the mechanical reliability of the third adhesive portion 43 can be improved.
[0149] 5, the metal support 10 has a contact region 10W in contact with the third adhesive portion 43. In this embodiment, the contact region 10W is a part of the second main surface 13. The contact region 10W preferably includes a first region W1 in contact with the first layer 1C, and a second region W2 that is connected to the first region W1 at a connection point R1 and in contact with the second layer 2C. This makes it possible to stop a crack that propagates between the first layer 1C and the second layer 2C toward the inside (i.e., the side away from the internal space 3a) at the connection point R1.
[0150] 5, the embossed portion 31 has a contact region 31W that contacts the third adhesive portion 43. The contact region 31W preferably includes a third region W3 that contacts the third layer 3C, and a fourth region W4 that is connected to the third region W3 at the connection point R2 and contacts the second layer 2C. This makes it possible to stop a crack that propagates inward between the second layer 2C and the third layer 3C at the connection point R2.
[0151] Furthermore, as shown in FIG. 5, the number of layers of the third adhesive portion 43 exposed from the opening 80b of the bottomed recess 80 is preferably greater than the number of layers of the third adhesive portion 43 disposed in the deepest part 80a of the bottomed recess 80. This makes the number of interfaces of each layer less on the deepest part 80a side than on the opening 80b side. This makes it possible to prevent cracks that tend to progress inward along the interfaces of each layer from reaching the deepest part 80a. In this embodiment, the number of layers of the third adhesive portion 43 exposed from the opening 80b is "3", and the number of layers of the third adhesive portion 43 disposed in the deepest part 80a is "1".
[0152] The third adhesive portion 43 can be formed by applying a paste containing Cr oxide onto at least one of the surfaces of the metal support 10 and the embossed portion 31, and then performing a heat treatment while the metal support 10 and the embossed portion 31 are in close contact with each other. The conditions for the heat treatment can be set appropriately, and can be, for example, 800° C. or higher and 1100° C. or lower, and 0.5 hours or higher and 24 hours or lower. The third adhesive portion 43 may be formed simultaneously with the first and second adhesive portions 41, 42.
[0153] (Modification of the embodiment) Although the embodiments of the present invention have been described above, the present invention is not limited to these, and various modifications are possible without departing from the spirit of the present invention.
[0154] [Variation 1] In the above first and second embodiments, the frame 20 and the interconnector 30 are separate members, but the frame 20 and the interconnector 30 may be an integral member. In this case, the chromium alloy container 3 does not include the second seal portion 50.
[0155] [Variation 2] In the first and second embodiments, the metal support 10 and the frame 20 are separate members, but the metal support 10 and the frame 20 may be an integral member. In this case, the chromium alloy container 3 does not include the first seal portion 40.
[0156] [Variation 3] In the first and second embodiments, the first adhesive portion 41 is configured by the first layer 1A, the second layer 2A, and the third layer 3A, but is not limited thereto. The first adhesive portion 41 may have a single layer structure, or a multi-layer structure of two layers or four or more layers. When the first adhesive portion 41 has a multi-layer structure, it is sufficient that at least one layer is configured by Cr oxide.
[0157] [Variation 4] In the first and second embodiments, the second adhesive portion 42 is configured by the first layer 1B, the second layer 2B, and the third layer 3B, but is not limited thereto. The second adhesive portion 42 may have a single layer structure, or a multi-layer structure of two layers or four or more layers. When the second adhesive portion 42 has a multi-layer structure, it is sufficient that at least one layer is configured by Cr oxide.
[0158] [Variation 5] In the second embodiment, the third adhesive portion 43 is configured by the first layer 1C, the second layer 2C, and the third layer 3C, but is not limited thereto. The third adhesive portion 43 may have a single-layer structure, or a multi-layer structure of two layers or four or more layers. When the third adhesive portion 43 has a multi-layer structure, it is sufficient that at least one layer is configured by Cr oxide.
[0159] [Variation 6] In the above first and second embodiments, the first seal portion 40 has the first adhesive portion 41 and the second adhesive portion 42, but it may have only one of the first adhesive portion 41 and the second adhesive portion 42.
[0160] In addition, the second seal portion 50 has the same configuration as the first seal portion 40, but may have a different configuration from the first seal portion 40. The second seal portion 50 may have only one of the first adhesive portion 41 and the second adhesive portion 42.
[0161] [Variation 7] In the above first and second embodiments, the metal support 10 and the frame body 20 are in close contact with or integrated with each other between the first adhesive portion 41 and the second adhesive portion 42, but this is not limited thereto. The metal support 10 and the frame body 20 do not have to be in close contact with or integrated with each other.
[0162] [Variation 8] In the above embodiment, an electrolytic cell has been described as an example of an electrochemical cell, but the electrochemical cell is not limited to an electrolytic cell. An electrochemical cell is a general term for an element in which a pair of electrodes are arranged so that an electromotive force is generated from an overall oxidation-reduction reaction in order to convert electrical energy into chemical energy, and an element for converting chemical energy into electrical energy. Therefore, the electrochemical cell includes, for example, a fuel cell that uses oxide ions or protons as a carrier.
[0163] [Variation 9] In the above embodiment, the chromium alloy container according to the present invention is applied to an electrochemical cell, but the chromium alloy container can be used for various purposes. For example, the chromium alloy container can be used as a methanation reactor for synthesizing methane from hydrogen and carbon dioxide. EXAMPLES
[0164] The following describes examples of the chromium alloy container according to the present invention, but the present invention is not limited to the following examples.
[0165] (Sample No. 1-7) Chromium alloy containers according to Samples No. 1 to 7 were produced as follows.
[0166] First, a paste containing at least one of Cr2O3 and Mn3O4 was applied to the outer periphery of the second main surface 13 of the metal support 10, and then a frame 20 was placed on the paste to produce a laminate. At this time, the Cr content in the metal elements in the Cr oxide constituting the adhesive joint was changed by changing the amounts of Cr2O3 and Mn3O4 charged, as shown in Table 1.
[0167] Next, the laminate was subjected to a heat treatment (1000°C, 1 hour) to form an adhesive portion made of Cr oxide from the paste, which adheres the metal support 10 and the frame 20. This completed a chromium alloy container with a single-layer adhesive portion. Note that in this example, the metal support 10 and the frame 20 were not welded or brazed.
[0168] Next, the composition of the Cr oxide that constitutes the bonded joint was analyzed with an EDS device to measure the Cr content among the metal elements in the Cr oxide. The Cr content at this time is shown in Table 1 as the "Cr content before heat durability test."
[0169] Next, a thermal endurance test was carried out by subjecting the chromium alloy container to a heat treatment (800°C, 1000 hours).
[0170] Next, the composition of the Cr oxide that constitutes the bond was analyzed with an EDS device to measure the Cr content of the metal elements in the Cr oxide again. The Cr content at this time is shown in Table 1 as the "Cr content after heat durability test."
[0171] [Table 1]
[0172] As shown in Table 1, in samples Nos. 3 to 6 in which the Cr content of the metal elements in the Cr oxide constituting the adhesive joint was set to 50 mol % or more, the change in the Cr content before and after the heat durability test was significantly reduced. This shows that by setting the Cr content of the metal elements in the Cr oxide constituting the adhesive joint to 50 mol % or more, it is possible to significantly prevent the Cr contained in the metal support 10 and the frame 20 from diffusing into the adhesive joint.
[0173] (Sample No. 8~14) Chromium alloy containers 3 (see FIG. 3) according to Samples No. 8 to 14 were fabricated as follows.
[0174] First, a paste containing Cr2O3, a paste containing MnCr2O4, and a paste containing Cr2O3 were successively applied to the outer periphery of the second main surface 13 of the metal support 10, and then a frame 20 was placed on the paste to produce a laminate. At this time, the application amount of each paste was changed to change the thickness ratio of each of the first to third layers 1A-3A and the first to third layers 1B-3B, as shown in Table 2.
[0175] Next, the metal support 10 and the frame 20 were lap-welded to be integrated with each other between the first adhesive portion 41 and the second adhesive portion 42.
[0176] Next, the laminate was subjected to a heat treatment (1000°C, 1 hour) to form the first and second adhesive parts 41, 42 made of Cr oxide from the paste, which bond the metal support 10 and the frame 20. This completed the chromium alloy container 3 equipped with the first and second adhesive parts 41, 42 of a three-layer structure.
[0177] Next, a heat endurance test was carried out by subjecting the chromium alloy container 3 to a heat treatment (800° C., 1000 hours).
[0178] Next, the chromium alloy container 3 was cut along the thickness direction to expose a cross section of the first adhesive portion 41 along the thickness direction.
[0179] Next, the thickness of each of the first to third layers 1A-3A was measured in the cross section of the first adhesive portion 41 by the method described in the above embodiment, and the thickness ratio of the thickest layer to the thinnest layer was calculated based on each measured thickness. The calculated thickness ratios are shown in Table 2.
[0180] Next, the cross section of the first adhesive portion 41 was observed by SEM to check for the presence or absence of cracks inside the first adhesive portion 41. Table 2 shows the results of checking for cracks.
[0181] [Table 2]
[0182] As shown in Table 2, no cracks occurred even after the heat endurance test in samples No. 8 to 12, in which the thickness ratio of the thickest layer to the thinnest layer among the first to third layers 1A to 3A was set to 5 or less. This shows that the mechanical reliability of the first adhesive portion 41 can be improved by setting the thickness ratio of the thickest layer to the thinnest layer among the first to third layers 1A to 3A to 5 or less.
[0183] Although not shown in Table 2, the same results as those of the first adhesive portion 41 were obtained in the second adhesive portion 42. [Explanation of symbols]
[0184] 1,1a Electrolysis cell 2 Cell body 3. Chromium alloy container 3a Interior space 6 Hydrogen electrode 7 Electrolytes 8. Reaction prevention layer 9 Oxygen electrode 10 Metal support 11 Supply hole 12 First main surface 13 Second main surface 20 Frame 30 Interconnector 31 Embossed section 40 First seal part 41 1st adhesive part 42 2nd adhesive part 43 3rd adhesive part 1A,1B,1C 1st layer 2A,2B,2C 2nd layer 3A,3B,3C 3rd layer 50 Second seal part
Claims
1. A chromium alloy container having an internal space, A first alloy member made of an alloy containing chromium; A second alloy member made of an alloy containing chromium; an adhesive portion that bonds the first alloy member and the second alloy member; Equipped with The adhesive portion is composed of an oxide mainly composed of chromium. Chromium alloy container.
2. The chromium content in the metal elements in the oxide is 50 mol% or more.
2. The chromium alloy container according to claim 1.
3. The oxide is composed of at least one of chromium oxide and chromium manganese oxide.
3. The chromium alloy container according to claim 1 or 2.
4. The oxide is crystalline.
2. The chromium alloy container according to claim 1.
5. The oxide has a spinel or corundum type crystal structure.
5. The chromium alloy container according to claim 4.
6. the bond includes a first layer disposed on the first alloy member and a second layer disposed between the first layer and the second alloy member; The oxide constituting the second oxide layer is different from the oxide constituting the first oxide layer.
2. The chromium alloy container according to claim 1.
7. the bonded joint includes a third layer sandwiched between the second layer and the second alloy member; the oxide constituting the third layer is the same as the oxide constituting the first layer, a thickness ratio of the thickest layer to the thinnest layer among the first layer, the second layer, and the third layer is 5 or less; 7. The chromium alloy container according to claim 6.
8. a contact region of a surface of the first alloy component in contact with the adhesive portion includes a first region in contact with the first layer and a second region in contact with the second layer; The second region is connected to the first region.
8. A chromium alloy container according to claim 6 or 7.
9. The adhesive portion is embedded in a bottomed recess formed between the first alloy member and the second alloy member, the number of layers of the adhesive portion exposed from the opening of the bottomed recess is greater than the number of layers of the adhesive portion disposed in the deepest portion of the bottomed recess; The chromium alloy container according to claim 8.
10. The adhesive portion is a seal for sealing the internal space.
2. The chromium alloy container according to claim 1.
11. The second alloy member has an embossed portion in contact with the first alloy member, The adhesive portion adheres the embossed portion to the first alloy member.
2. The chromium alloy container according to claim 1.
12. The chromium alloy container according to claim 1 ; a cell body disposed on the chromium alloy vessel; Equipped with the first alloy member has a plurality of communicating holes that communicate with the internal space, the cell main body is disposed on the first alloy member so as to cover the plurality of communication holes; Metal-supported electrochemical cells.
Citation Information
Patent Citations
Joining material of solid electrolyte fuel cell stack and its joining method
JP1996130022A
Inorganic adhesive, semiconductor device using the same and its production
JP1997217039A
Solid electrolyte fuel cell
JP1998106596A
Sealing material for low-temperature operation solid oxide fuel cell
JP2004039573A
Metal support solid oxide fuel cell and manufacturing method therefor
JP2016207630A